Environmental indicators of urban green areas for management in two cities of Costa Rica - Morales-Cerdas, Vanessa (2018)
Environmental quality contributes to the physical and mental well-being of the population. In this way, the green areas (GA) of the cities are essential spaces for coexistence, sports, socialization, and recreation, among others. The objective of this research was to determine the environmental conditions of green areas, using indicators as tool for urban management in two cities of Costa Rica. The study area corresponded to the districts of Heredia and Carmen, Costa Rica. The existing GA were determined using Rapid Eye satellite images, 2012 through spatial analysis and remote sensing. Eleven indicators of urban green areas were applied, the species was identified, the height, the diameter at breast height (DBH) and the number of trees in parks and streets were measured. In addition, surveys were conducted to users of public GA, on issues related to accessibility and use of GA. Five types of GA were identified in Carmen and six in Heredia. The percentage of public and private green areas corresponded to 36 % and 64 % in Carmen and 13 % and 87 % in Heredia respectively. The green area per capita (m2/hab) was 24.6 in Carmen and 2.7 in Heredia. Sixty-two species of trees were identified in the Carmen parks and 23 in Heredia. There were 1 105 trees of 61 species in the streets, sidewalks and avenues of Carmen and 278 individuals of 47 species in Heredia. Regarding the existence of riparian vegetation, it was determined that Pirro, Burrio, Torres and Negritos streams maintain 82, 51, 81 and 14 % of margin protection areas in conforming use. Eleven of the public GA’s were evaluated, nine presented a high physical accessibility. In both districts, the surveyed citizens indicated the necessity to have more GA, highlighting the recreational, ecological and touristic value of these spaces. It is concluded that the indicators of urban green areas showed that there are differences between the environmental conditions in both of the evaluated cities. In addition, the applicability of the indicators is feasible as an input for the sustainable environmental management of urban ecosystems.